Climate change reshuffles northern species within their niches - Antão Laura H.; Weigel Benjamin; Strona Giovanni; Hällfors Maria; Kaarlejärvi Elina; Dallas Tad; Opedal Øystein H.; Heliölä Janne; Henttonen Heikki; Huitu Otso; Korpimäki Erkki; Kuussaari Mikko; et al. (NATURE PORTFOLIO, 2022)
Climate change is a pervasive threat to biodiversity. While range shifts are a known consequence of climate warming contributing to regional community change, less is known about how species' positions shift within their climatic niches. Furthermore, whether the relative importance of different climatic variables prompting such shifts varies with changing climate remains unclear. Here we analysed four decades of data for 1,478 species of birds, mammals, butterflies, moths, plants and phytoplankton along a 1,200 km high latitudinal gradient. The relative importance of climatic drivers varied non-uniformly with progressing climate change. While species turnover among decades was limited, the relative position of species within their climatic niche shifted substantially. A greater proportion of species responded to climatic change at higher latitudes, where changes were stronger. These diverging climate imprints restructure a full biome, making it difficult to generalize biodiversity responses and raising concerns about ecosystem integrity in the face of accelerating climate change.The authors analyse four decades of distribution data for various taxonomic groups to understand the shift of species within their climatic niches and the changing influences of different climate factors. The diverse and diverging climate imprints raise concerns about future ecosystem integrity.